Deterministic positioning of few aqueous colloidal quantum dots - Pambudi, Muhammad Tegar (2024)
Emerging quantum technologies that critically require the integration of quantum emitters on photonic platforms are hindered by the control over their position, quantity, and scalability. Herein, we describe a facile strategy to deposit aqueous silica-coated quantum dots (QDs) in a template of polymethyl methacrylate (PMMA) nanoholes that leverages saturated ethanol vapor drop-casting and subsequent lift-off of the template. Ethanol vapor incorporation into water droplets during the drying process reduces the meniscus contact angle, which increases capillary forces and enhances particle confinement within the pinning contact region. Furthermore, induced Marangoni flow controls the particle transport dynamics inside the droplets, making large-scale deposition possible. Controlling the hole diameter of the template demonstrates changes in the number of QDs per hole, which is consistent with the Poissonian distribution with the best results of ∼40% single-particle yield from an ∼80% total site occupancy. This method employs a simple setup, eliminating the need for intricate optimization, yet offers the potential for deterministic patterning within complex photonic platforms.